A Hierarchical Short Microneedle-Cupping Dual-Amplified Patch Enables Accelerated, Uniform, Pain-Free Transdermal Delivery of Extracellular Vesicles - Minwoo Song; Minji Ha; Sol Shin; Minjin Kim; Soyoung Son; Jihyun Lee; Gui Won Hwang; Jeongyun Kim; Van Hieu Duong; Jae Hyung Park; Changhyun Pang (Nano-Micro Letters)
Highlights A bio-inspired dual-amplified patch (MN@EV/SC) was fabricated by integrating extracellular vesicle-loaded microneedles with a soft suction chamber for effective transdermal delivery. The MN@EV/SC system achieved an exceptional penetration depth of 290 μm, while minimizing plasma corticosterone levels with short microneedles, ensuring patient comfort through pain-free application. This system showed the potential for dermatological application by revitalizing dermal fibroblasts, and enhancing collagen synthesis through effective delivery of extracellular vesicles while preserving their biological functionality.